A Case Study for E-Readiness Among the Community of Kg. Lembah Palas - Muttamah, Sathivelu (2009)
Malaysia has evolved drastically in the electronic field over the last decade. E-government and its partner in the electronic age, e-participation, have over the course of the past decade moved from concept to reality, at least at some level, and in the last 4-6 years. In the Ninth Malaysian Plan, many benefits in bridging the digital divide among the rural community have been outlined. Though there is a question of whether the rural communities are actually enjoying the benefits of this so called digital channel to further economic and social development. For any electronic participation to happen, the community has to be e-ready first. This is a case study involving the community of Kg. Lembah Palas, a small village nearby the town of Changlun in the State of Kedah. A study of e-readiness will provide a better understanding as to why e-participation of the rural community is still in the miniature proportion in comparison to their urban counterparts. The e-readiness of this community is in comparison to the e-readiness of the nation by the Economist Intelligence Unit.